Automatic washroom light - Othman, Muhammad Shadzrin; Mohd Salehuddin, Mohd Firdaus (2016)
The project of automatic washroom light is being produce because to encounter the problem that we face in the world today. It have been say by someone that the world may be rise in electricity tariff rate. Today it also expected that the electricity cost of every household and building will also. There are many cases where people forgot to turn OFF the light when they exits the washroom. When this happen, the people will lack in energy saving awareness. There also a case were children involved in accidents due to lack awareness of electricity safety. So this project mainly to teach people to save more energy so it can help the earth. The project will use a component that will make the user easier in life. For example like limit switch. The function of limit switch is similar to the ordinary switch but the different is how it being use. The automatic washroom light will 1st being construct on the breadboard and in the simulation Proteus. The circuit that will be test whether it can produce the real project that being decide. If the circuit have no correction to do or modifying, then it will transfer to the PCB. In the process of making this project success, the data or result will be taken every time. This is to ensure that our project get the actual output that being set by in the simulation. If there is a slight problem in the circuit, this automatic washroom light will not be a successfully project. So to overcome this problem, it only take a small action which is troubleshooting on every component and connection. Circuit testing and troubleshooting can be described as process of inspecting a problem or errors occurred when our project is carried out. This is important because it will determine whether the project become success or failure. If there is an error that happen in our circuit, it can be eliminate by doing some troubleshooting. Troubleshooting can be done by inspecting the voltage and current flow in the circuit.